INTEGRATING SHARIA VALUES AND MEDICAL STANDARDS IN SAFE AND ETHICAL SUNNAH CUPPING PRACTICES - Andik Isdianto; Novariza Fitrianti; Abdul Hamid Arif; Wahyudi Widada (PT. Jurnal Center Indonesia Publisher, 2025)
Sunnah cupping therapy (hijamah) is a form of prophetic medicine that combines spiritual and therapeutic dimensions but often lacks adherence to clinical safety standards. This study aims to analyze the urgency of integrating Sharia values—particularly maqashid shariah (protection of life) and la dharara wa la dhirar—with emergency medical protocols in sunnah cupping practice. The research uses a normative-qualitative literature review method. Data were collected from recent academic sources and analyzed through content analysis to develop an ethical and procedural framework. Findings reveal that sunnah cupping carries clinical risks such as infection, bleeding, and vasovagal shock when performed without medical protocols. The integration of Sharia and medical principles is operationalized through emergency training, Islamic-based SOPs, and education-regulation mechanisms rooted in maqashid. Core Islamic ethics—such as ikhlas (intention), amanah (trust), and tathir al-adawat (sterilization)—are essential moral pillars within the clinical service model. This study concludes that the integration of Sharia values with emergency medical preparedness is a critical need in the practice of sunnah cupping. The study recommends the development of standardized curricula, clinic certification, and first aid (CPR) training for therapists to ensure safety, professionalism, and religious legitimacy.